Persuasive Strategies for Encouraging Social Interaction for Older Adults. Issue 3 (3rd March 2016) - Vargheese, John Paul; Sripada, Somayajulu; Masthoff, Judith; Oren, Nir
Abstract : Social isolation among older adults represents a significant societal challenge in which persuasion offers a potential solution. To develop a persuasive interactive system for this purpose, we conducted a modeling study with carers to discover how persuasion is used to encourage social interaction among older adults. From an analysis of the results, we identified and defined effective persuasive strategies grounded in theories of persuasion and developed a computational model for applying them. This article reports the findings from an evaluation of the generalizability of this model and presents a revised version based on these results. The article concludes with a discussion on possible domain-specific conceptual features between the model evaluated and the revised model developed.